Virtual patients with substance use disorders in healthcare professional education: a scoping review - Morvannou, Adèle; Allami, Youssef; Jobin, Emilie Y (Canadian Medical Education Journal, 2024)
Background and Objective: Virtual patient simulations are cost-effective methods for training health professionals. Yet, this teaching method is rarely used with clinicians who work or plan on working with people with substance use disorders. This scoping review summarizes the current state of the literature concerning virtual substance use disorder patient simulations in health professionals’ training and provides suggestions for future directions. Methods: Online databases were searched for peer-reviewed articles published between January 2010 and June 2024. Results: Twelve studies were included. The development, administration, and evaluation of performance of the simulations are diverse. Most simulations aim to develop screening, brief interventions or referring skill, they target a variety of health professionals’ disciplines and report positive learning outcomes. Virtual simulations have good acceptance rates from learners. Conclusions: Enhancing the diversity of clinical skills and patient populations portrayed in simulations, alongside adherence to best practices in simulation development and implementation is suggested to optimize training outcomes in this critical area of healthcare education.